Intake, gain and carcass traits of Hereford and Simmental bulls offered total mixed rations based on red clover and whole-crop barley silages - Huuskonen, Arto; Pesonen, Maiju; Manni, Katariina (Scientific Agricultural Society of Finland, 2024)
Total mixed rations (TMR) based on red clover silage (RS), whole-crop barley silage (BS) and mixture of RS and BS were fed to thirty Hereford (HF) and thirty Simmental (SI) bulls. The proportion (g kg-1 dry matter (DM)) of the silages in the TMRs were as follows: (1) RS (600); (2) BS (600); (3) RS (300) and BS (300). Concentrate proportion was 400 g kg-1 DM. Breed × feeding interactions were observed for intake parameters. Replacing RS by BS tended to increase DM and nutrient intake more in the SI compared to the HF breed. For growth performance a significant quadratic effect was observed for the dietary treatments; both the live weight gain and carcass gain were the highest when RS was partially replaced by BS. There were no differences in carcass weight, dressing proportion or carcass conformation among the dietary treatments. However, replacing RS by BS increased carcass fatness. The SI bulls had higher growth rate and they produced better conformed carcasses and less fat compared to the HF bulls.
Keywords: beef production; feeding; growth performance; Hordeum vulgare; Trifolium pratense